Risk factors for hepatocellular carcinoma in turkey - (:unkn) unknown (My University, 2001)
The contribution of hepatitis B, hepatitis C, and excess alcohol intake to the development of hepatocellular carcinoma in Turkey was assessed. The study was conducted through a questionnaire sent to seven major medical referral centers in different regions of Turkey and is based on 207 patients seen in the period 1994-1997. Of the seven centers, two were located in West Turkey (54 patients), two were in Central Turkey (85 patients), and two were in south and southeast Turkey (68 patients). In 196 of the 207 patients (94.7%), there was a history of chronic liver disease, and in 180 patients (87%) liver cirrhosis was documented. Of the 207 patients, 116 (56%) had hepatitis B, 48 (23.2%) had hepatitis C, and 33 (15.9%) had a history of excess alcohol intake. Anti-delta testing was available in 69 of 116 patients with hepatitis B, and anti-HDV was positive in 13 of these patients (13/69, 18.8%). Of the 33 patients with a history of heavy alcohol intake, 18 had concomitant chronic viral hepatitis infection, and alcohol alone was the etiology of hepatocellular carcinoma in only 15 cases (7.2%). The distribution of etiologic factors was not homogenous in different geographical regions in Turkey. In central, south, and southeastern Turkey, the predominant etiology of hepatocellular carcinoma was hepatitis B, whereas in western Turkey the impact of hepatitis B, hepatitis C, and alcohol was similar. This study indicates that hepatitis B virus infection is the leading cause of hepatocellular carcinoma in Turkey, followed by hepatitis C infection and alcoholic liver disease.
Keywords: Alcohol; Hepatitis B; Hepatitis C; Hepatocellular carcinoma; Turkey